Writing Development in DHH Students: A Bimodal Bilingual Approach. (14th December 2022) - Gärdenfors, Moa
Abstract: This article describes the lexical and syntactic development of written narratives in 24 deaf and hard-of-hearing (DHH) students aged between 8 and 18 and takes into account how their varying linguistic backgrounds may predict their written performance. All participants use spoken Swedish, but the study also considers their proficiency in Swedish Sign language, which ranged from zero to fluent. Their narrative texts were analyzed in regard to syntax and lexicon, which demonstrated a strong developmental trend in which increased age predicted more complex texts. Age of acquisition did not predict any writing outcome, which is suggested to occur because all participants were exposed to language early, that is, within the critical time window for language acquisition. Sign language proficiency showed a tendency to predict adjective density and number of clauses, which encourages future research in this area, especially since this connection argues for the benefits of early access to a language and the positive relationship between sign language proficiency and writing.